Infância, corpo, educação e cibercultura : crianças e a produção de imagens nas redes sociais - Zequetto, Antonio Cleber (2018)
The deep cultural changes in society affect, especially since the last decade, the ways in which subjects learn, relate and constitute themselves. This continuous growth of technological resources competes for new knowledge to be produced with access to the internet. With this digital advancement, the child's relational environment is constantly being redefined. In this direction, this research, developed as part of the research line "Childhood, Youth and Contemporary Culture: rights, policies and diversity" and the Research Group "Childhood, Youth and Contemporary Culture" (GEIJC) and the social place of the child in the context of digital technologies. Its main objective is to analyze the discourses of a group of children, aged between 8 and 13 years, on the images published on the virtual platform and produced on wheels of conversations focused on this theme, occurring in the school context. Intervention research was adopted as a methodology when we took as a starting point the alterity established in the relationship between children and adults. The theoretical-methodological framework is based on the concepts of dialogism and alterity of Mikhail Bakhtin, which allow the understanding of language as a dynamic process of interlocution and production of meanings. The new configurations in the context of cyberculture, as well as the senses, knowledge and social practices that children construct when they relate to digital media, are the focus of this research. Based on the analyzes of the discourses of the children participating in the research and the authors that base this research, such as Haraway (1991), Buckingham (2007), Corsaro (2011), Le Breton (2011), Louro , among others, seeks to reflect on the subjective constitutions and processes of exteriority of the child's body, in order to problematize the convergence of the social phenomena that emerge in the contemporary, the challenges for an education in the digital age, as well as the cultural experiences that children share in this current design in which childhood is configured.